Analysis of ABCG2 pharmacology and oligomerisation by solution based fluorescence correlation spectroscopy - Horsey, Aaron J. (2019)
ABCG2 is a human ATP-binding cassette (ABC) transporter. It has a broad substrate range that includes a number of small molecule drugs as well as endogenous metabolites. With its expression in barrier tissues (e.g. kidney epithelium) ABCG2 has a strong influence on pharmacokinetics in addition to other physiological roles (e.g. urate excretion). ABCG2 is also expressed in several tumours and confers resistance to various chemotherapy agents. The detailed interactions and mechanisms that support such polyspecificity are not well-established and progress in understanding ABCG2 pharmacology has been limited.